Corynebacterium Species of the Conjunctiva and Nose: Dominant Species and Species-Related Differences of Antibiotic Susceptibility Profiles. Issue 11 (November 2020) - Hoshi, Saichi; Todokoro, Daisuke; Sasaki, Takashi
Abstract : Purpose: Nondiphtherial Corynebacterium species are normal residents of human skin and mucosa, including the conjunctiva and nose, but can cause conjunctivitis and keratitis. Recently, resistance against various classes of antibiotics has been reported in Corynebacterium . The present study investigated the type of species and antibiotic susceptibilities of the conjunctival and nasal Corynebacterium species. Methods: This study examined 183 strains of Corynebacterium species that were isolated from patients undergoing preoperative examinations for cataract surgery. Species were identified by RNA polymerase β-subunit-encoding gene ( rpoB ) sequencing. Antibiotic susceptibility tests were performed by the microdilution method according to the Clinical and Laboratory Standards Institute standard method M45. Results: Corynebacterium macginleyi was the most predominant species (84%; 46 of 55) in the conjunctiva. The 2 major species in the nasal cavity were Corynebacterium accolens and Corynebacterium propinquum (44% and 31%, respectively), followed by Corynebacterium pseudodiphtheriticum (8%), Corynebacterium jeikeium (7%), and C. macginleyi (3%). In contrast to other nasal Corynebacterium species, only C. macginleyi showed a high susceptibility to macrolides. However, among nonconjunctival Corynebacterium species, C. propinquum, was unique in having a high resistance rate to levofloxacin (29%), comparable with that observed in C. macginleyi (36%). Penicillin G and tobramycin showed good susceptibility in almost all strains. Conclusions: Drug resistance against fluoroquinolones and macrolides was observed in Corynebacterium species, with the antibiotic susceptibility profiles correlating with differences of the species and niche. Nasal and conjunctival Corynebacterium profiles of drug resistance suggest habitat segregation strictly at the species level.